Capturing the Performance of Indonesian Sharia Stock Index (ISSI) and Composite Share Price Index (IHSG) Jakarta Period 2016-2019 - Muhammad Hanif al-Hakim (Universitas Muhammadiyah Malang, 2020)
This study aims to compare the performance of Indonesia Sharia Stock Index (ISSI) and Composite Share Price Index (IHSG) Jakarta over bullish dan bearish period 2016-2019. This research is descriptive quantitative using natural log and standard deviation calculation. The data retrieved from Financial Service Autority. The finding show that indexes whose volatility values are high does not always generate high positive returns. In addition, the performance of the two indices showed the same pattern in both bullish and bearish periods despite the differences in some conditions and systems.